2020
DOI: 10.1080/17508487.2020.1733037
|View full text |Cite
|
Sign up to set email alerts
|

Lessons in character education: incorporating neoliberal learning in classroom resources

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
0
17
0
4
Order By: Relevance
“…Moreover, this activity benefits students to form positive student behavior, including the students' morals. Another study confirmed the effectiveness of teaching strategy on student affective domain [19][20][21][22]. It is presented that the implementation of cooperative learning methods can promote a positive student attitude.…”
Section: Student Charactermentioning
confidence: 74%
“…Moreover, this activity benefits students to form positive student behavior, including the students' morals. Another study confirmed the effectiveness of teaching strategy on student affective domain [19][20][21][22]. It is presented that the implementation of cooperative learning methods can promote a positive student attitude.…”
Section: Student Charactermentioning
confidence: 74%
“…Attempt to involve parents as partners in character education programs in educational institutions [18]. Jerome and State good social progress is achieved by the young generation in collective action [19]. Said that character education helps students build morality and character through the interaction of the learning environment [20].…”
Section: Previous Studies Related To the Impact Of Art Education Withmentioning
confidence: 99%
“…The author's voice will have transformative power (Black, 2019;Matousek, 2017), echoing significant changes embodied in various aspects of life, particularly creative writing on political, economic, educational, tolerance, multi, and socio-cultural topics. In the digital age, the author's voice is the voice of character education (Jerome & Kisby, 2020;Jerome & Kisby, 2019). Reflective journal writing leads to transformative practice within communities or groups of writers, as shown in the diagram below.…”
Section: The Attributes Of Reflective Journal Writing That Foster Transformative Practicesmentioning
confidence: 99%